Epitope dominance studies with serotype O foot-and-mouth disease - Borley, DW (2012)
Foot-and-mouth disease virus (FMDV) is an economically devastating and highly contagious livestock pathogen. It exists as seven serotypes, comprising numerous antigenically distinct subtypes. The large amount of antigenic heterogeneity has confounded attempts at developing broadly reactive vaccines. In order to overcome this issue the fundamentals of the interactions between the virus and the host humoral immune response must first be understood. Previous work in this area using monoclonal antibody (mAb) escape mutants has identified five antigenic sites for the O serotype and efforts have been made to quantify their relative importance. However, this does not represent a complete picture of serotype O antigenicity. The work conducted in this thesis demonstrates the role of a limited number of dominant substitutions in mediating the antigenic diversity of serotype O Foot-and-Mouth disease virus. Two alternative but complementary methods for identifying epitopes were developed. The first used a mathematical model to analyse newly generated serological and sequence data from 105 viruses, cultured for this purpose (and cross-reacted to 5 reference antisera), in the context of an existing crystallographic structure to identify and quantify the antigenic importance of sites on the surface of the virus. The second approach was purely structural, using existing B cell epitope prediction tools to develop a method for predicting FMDV epitopes using existing crystallographic structures of FMDV. These techniques were validated by the use of reverse genetics, which confirmed the impact on cross reactivity of two predicted novel serotype O antigenic residues, with a further four novel residues identified by looking in depth at the interactions between two genetically close, but antigenically distant viruses. This increased knowledge of the antigenic composition of serotype O FMDV contributes to our understanding of the nature of vaccine efficacy and the breadth of protection, which, in the longer term, will aid in the goal of developing vaccines to better protect livestock from such a highly antigenically variable disease.